Synergistic interaction between interferon-alpha and interferon-gamma through induced synthesis of one subunit of the transcription factor ISGF3. - Levy, D E (1990)
Interferon-alpha (IFN alpha) and interferon-gamma (IFN gamma) each induce in susceptible target cells a state of resistance to viral replication and reduced cellular proliferation, presumably through different mechanisms: these two polypeptides are unrelated by primary sequence and act through distinct cell-surface receptors to induce expression of largely non-overlapping sets of genes. However, acting in concert, they can produce synergistic interactions leading to mutual reinforcement of the physiological response. In HeLa cells, this synergistic response was initiated by cooperative induction of IFN alpha stimulated genes (ISGs). These normally quiescent genes were rapidly induced to high rates of transcription following exposure of cells to IFN alpha. Although they were only negligibly responsive to IFN gamma, combined treatment of cells with IFN gamma followed by IFN alpha resulted in an approximately 10-fold increase in ISG transcription. ISG transcription is dependent upon ISGF3, a positive transcription factor specific for a cis-acting regulatory element in ISG promoters. IFN gamma treatment induced increased synthesis of latent ISGF3, which was subsequently activated in response to IFN alpha to form approximately 10-fold higher levels than detected in cells treated with IFN alpha alone. ISGF3 is composed of two distinct polypeptide components, synthesis of one of which was induced by IFN gamma, increasing its cellular abundance from limiting concentrations to a level which allowed formation of at least 10 times as much active ISGF3. Cell lines vary in their constitutive levels of the inducible component of ISGF3 and in the ability of IFNs to increase its synthesis.(ABSTRACT TRUNCATED AT 250 WORDS)